Methylomic analysis of salivary DNA in childhood ADHD identifies altered DNA methylation in VIPR2. (25th August 2015) - Wilmot, Beth; Fry, Rebecca; Smeester, Lisa; Musser, Erica D.; Mill, Jonathan; Nigg, Joel T.
Abstract : Background: Peripheral epigenetic marks hold promise for understanding psychiatric illness and may represent fingerprints of gene–environment interactions. We conducted an initial examination of CpG methylation variation in children with or without attention‐deficit/hyperactivity disorder (ADHD). Methods: Children age 7–12 were recruited, screened, evaluated and assigned to ADHD or non‐ADHD groups by defined research criteria. Two independent age‐matched samples were examined, a discovery set ( n  = 92, all boys, half control, half ADHD) and a confirmation set ( n  = 20, half ADHD, all boys). 5‐methylcytosine levels were quantified in salivary DNA using the Illumina 450 K HumanMethylation array. Genes for which multiple probes were nominally significant and had a beta difference of at least 2% were evaluated for biological relevance and prioritized for confirmation and sequence validation. Gene pathways were explored and described. Results: Two genes met the criteria for confirmation testing, VIPR2 and MYT1L ; both had multiple probes meeting cutoffs and strong biological relevance. Probes on VIPR2 passed FDR correction in the confirmation set and were confirmed through bisulfite sequencing. Enrichment analysis suggested involvement of gene sets or pathways related to inflammatory processes and modulation of monoamine and cholinergic neurotransmission. Conclusions: Although it is unknown to what extent CpG methylation seen in peripheral tissue reflect transcriptomic changes in the brain, these initial results indicate that peripheral DNA methylation markers in ADHD may be promising and suggest targeted hypotheses for future study in larger samples.